MELACAK AKAR SEJARAH SISTEM DAN LEMBAGAAN PENDIDIKAN ISLAM PADA MASA RASULULLAH SAW (PERIODE MEKKAH DAN MADINAH - Usman DP (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2021)
In a historical perspective, Islamic education as a sub system of the education system in general way only known after the sending of the Prophet Muhammad SAW has a messenger of Allah SWT. The retise unders prophet Muhammad SAW covers the system that axixts in the life on the universe, Islamic education refers to Islamic values. Therefore, the Islamic education system has a fundamental difference with the education system built by education both in the East and West . During the leadership of the prophet Muhammad SAW, Islamic education was built on a monolothic basis, which was sourced from revelation, namely the Qur’an and Hadith. Therefore, Islamic education is not known has a dichotomous term, the separation between religious education and general education. Keywords: Islamic Education System and Institution, Rasulullah SAW.